1990
DOI: 10.1002/yea.320060308
|View full text |Cite
|
Sign up to set email alerts
|

The start gene CDC28 and the genetic stability of yeast

Abstract: The cdc28-srm mutation in Saccharomyces cerevisiae decreases spontaneous and induced mitochondrial rho- mutability and the mitotic stability of native chromosomes and recombinant circular minichromosomes. The effects of cdc28-srm on the genetic stability of cells support the hypothesis that links cell cycle regulation in yeast to changes in chromatin organization dependent on the start gene CDC28 (Hayles and Nurse, 1986).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Decreased mitotic stability is displayed by a number of cdc28 alleles (10,33). These alleles would be good candidates for mutants that have poor p40-Cdc28 interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased mitotic stability is displayed by a number of cdc28 alleles (10,33). These alleles would be good candidates for mutants that have poor p40-Cdc28 interactions.…”
Section: Resultsmentioning
confidence: 99%
“…They began with a strain producing 50% petites and selected four mutations giving rise to a lower level of petites (Table 10) (see "No compromise" below). In further studies, Devin et al (67) found a fifth mutation, shown to be allelic to CDC28. This gene encodes the protein kinase called p34 cdc28 (p34 cdc2 in Schizosaccharomyces pombe and other eucaryotes) which, in yeasts, controls both the G 1 /S and G 2 /M transitions of the cell cycle by interactions with specific cyclins (reviewed in reference 181).…”
Section: Mtdna and The Cell Cycle: A Black Boxmentioning
confidence: 95%
“…Even subtle changes in Cdc28 function affecting mitotic progression may impinge on chromosome stability. Indeed, mutations of several Cdc28 partners and substrates have been associated with genomic instability, whereas mutations of Cdc28 itself, such as cdc28-1N (11), cdc28-srm (12), and cdc28-5M (13), are associated with relatively nonspecific defects in chromosome segregation and/or mitotic checkpoint control. Paradoxically, current models suggest that Cdc28 and its partners are only passive effectors of the mitotic surveillance pathways (14).…”
mentioning
confidence: 99%